Building’s Constructions and Structures. Part II. Changes of Structures in Supporting Structures of Buildings - Lámer, Géza (International Journal of Engineering and Management Sciences, 2017)
In the Part II. we deal with the changes of structures in supporting structures of buildings. The changes of the structure we will connected with new materials or new approach. We deal with two problems. First is the formations and change of the vault. The second is the change of the supporting structure of buildings in case of using new materials with bending or only stretching resistance.